Let T be Tom's age and F be his father's age.

Right now F = 3T because father is three times as old as Tom.

Four years ago, their ages were F-4 and T-4. So:

4 (T-4) = F-4

If you do the math there, you get

4T - 16...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Let T be Tom's age and F be his father's age.

Right now F = 3T because father is three times as old as Tom.

Four years ago, their ages were F-4 and T-4. So:

4 (T-4) = F-4

If you do the math there, you get

4T - 16 = F -4

So now you substitute in the value of F that we set up earlier. And you get

4T - 16 = 3T - 4

So now it's pretty simple.

4T = 16 + 3T - 4

T = 12

So Tom is 12. His father is 36.

Four years ago, he was 8 and Dad was 32.